'Good-bye Pompey, komm bald zurück': Stevie Smith's Vision of Germany in Novel on Yellow Paper. Issue 3 (2nd October 2018) - Wünnenberg, Barbara
Abstract: In Stevie Smith's debut novel Novel on Yellow Paper, set in 1936, the narrator Pompey Casmilus recalls several trips to Germany she made in the years shortly before the rise of the Hitler regime. The memories of these German travels are linked to Pompey's love affair with a Swiss-German student named Karl with whom she has spent time in both England and Germany. The essay explores the significance of the German theme in the novel. This theme emerges in Pompey's memories of Germany and Karl, which at first glance appear to be random moments of recollection. However, the German theme also asserts itself in what I call Pompey's German voice, a distinct narrative voice that uses a specific German vocabulary and mimics German speech patterns, which appears at different points throughout the novel and is not exclusively linked to Pompey's memories of Germany. The essay argues that this narrative voice, the Karl-Pompey romance plot and the narrator's obsessive concern with Jewishness combine into an exploration of the Anglo-German relationship in the inter-war years and the attraction which Germany held for some British visitors during the 1920s and early 1930s, an attraction which is linked to previous literary explorations of the country by British writers such as D. H. Lawrence and which by 1936 has taken on an ominous significance as Pompey observes from afar the atrocities being committed within Germany in the name of the Hitler regime.